Reading the visual form of Malaysian comics art / Karna Mustaqim - Mustaqim, Karna (Institute of Graduate Studies, UiTM, 2016)
People nowadays lives in a convergence culture who witnessing how the meeting of old and new media open up new possibilities in the contemporary culture. One of cultivates popular culture in late nineteenth century is the medium of comics. The amusement of comics invited its reader – young or adult – to be immersed into its world. Taking underrated subject matter in popular visual culture such as comics is an intriguing task. While people would agree that cartoons are valuable reflection of society, yet it is an arduous task to take since it was not yet count as a truly significant scholarship. The lack of appreciation made the richness of local comics unseen and as an important contemporary visual culture remains undiscovered. Articulating the expression of contemporary Malaysian comics is not even more a lucid mission…